OTOMATISASI TEKNOLOGI SMART HOME MENGGUNAKAN ARDUINO BERBASIS INTERNET OFF THINGS (IoT) - Benny Suhendar; Rizki Fatullah (Journal of Innovation And Future Technology (IFTECH), 2020)
"IOT-based Interactive Monitoring and Monitoring System for home automation" is another technological advance that can control and filter gadgets or other devices to control home automation remotely. Every automation business that uses an inserted system such as a PIC microcontroller provides an intelligent, inexpensive energy protection system, for homes, schools, hospital facilities or others. The main objective of this research is to plan and provide an interesting implementation point of IoT for home applications and also other means to control or control existing equipment in the house such as turning on / off lights, fans, gas, patterns, doors and others by using sensors, which serve to control. In general, we know that we use a number of equipment in homes, theaters, shopping centers, Convention Centers, Hotels and other facilities whose equipment we connect directly to electricity and consume power. Because of this, some equipment has failed due to excess voltage. Here, we use several components to control the excess voltage. In this model we use a micro controller (ATMEGA328P), which is connected to a nodemcu, 4-channel relay board, and liquid crystal display (LCD). Here the input is given to the micro controller via the LCD to display the temperature. The output of this signal is given to the micro controller where the pin becomes active when there is a problem finding room temperature. A 4-channel relay board is connected to control large equipment, meanwhile we connect switches to operate and nodemcu (Wi-Fi module) to control with remote access.